The Longest Day : June 6, 1944 - Ryan, Cornelius (Lahore National Book foundation, 1962)
On June 6, 1944, the Allied Invasion of France marked the beginning of the end of Nazi domination over Europe. The attack involved 3,000,000 men, 11,000 planes and 4,000 ships, comprising the largest armada the world has ever seen. A vivid hour-by-hour re-creation of this historic event. Told from the perspectives of both sides, it is a fascinating look at the massive preparation, mistakes and random events that determined the outcome of one of the biggest battles in history.
Includes Notes and Index.
Keywords: World War, 1939-1945